What's your Finsta pare? analyzing the self-preservation of male Gen Z college students on their primary and secondary Instagram accounts - Rabena, Mikaehla Royo
Finstas or dump accounts as online intimate spaces may be seen as a strategic response to the pressure of conforming to social norms in front of a broad and vague online audience. Existing finsta research, however, has gathered data from a predominantly female respondent base. As a response, this research aimed to uncover the experiences of the minority of the practice– the male population, by analyzing how male Gen Z college students display their self-presentation in both their primary and secondary Instagram accounts. The analysis primarily focused on the general attitudes, emotions, and motivations, as well as the decision-making, creative, and thought processes of the users on self-presentation and curation online by examining their use, perception, and behavior in this reconfigured platform.